2022
DOI: 10.1007/s44202-021-00016-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of attachment style on interpersonal learning in substance use psychotherapy groups

Abstract: Substance Use Disorders (SUDs) are prevalent, long-term conditions, commonly treated via group intervention. Additionally, interpersonal learning (IL) is a therapeutic factor unique to group treatment programs, which has been associated with successful group therapy outcomes. While previous research has suggested attachment styles may predict experiences of IL within groups, research in this area is limited. Therefore, this study aims to investigate if attachment style impacts IL, within SUD group treatment pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The attachment style as a research variable shows relatively high stability over time, and the online psychotherapy itself was short (only 10 weeks). Skentzos et al ( 67 ) indicated that the group may be understood as a social microcosm that provides members with corrective emotional experiences. The authors also emphasized that the therapeutic effect is mediated by group cohesion and can also be moderated by the attachment style of the psychotherapist ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…The attachment style as a research variable shows relatively high stability over time, and the online psychotherapy itself was short (only 10 weeks). Skentzos et al ( 67 ) indicated that the group may be understood as a social microcosm that provides members with corrective emotional experiences. The authors also emphasized that the therapeutic effect is mediated by group cohesion and can also be moderated by the attachment style of the psychotherapist ( 68 ).…”
Section: Discussionmentioning
confidence: 99%